Revitalisasi Pendidikan Buddhis Melalui Manajemen Strategis Berbasis Dhamma - Alfred Wijaya; Meri Meri; Kabri Kabri; Partono Partono (Dhammavicaya : Jurnal Pengkajian Dhamma, 2025)
Buddhist education in Indonesia faces structural and cultural challenges that threaten its sustainability, such as declining student numbers, limited human resources, and minimal funding. This study aims to develop a Buddhist education management model based on Dhamma principles (Paññā, Sīla, Viriya) integrated with a contemporary strategic approach. Using descriptive-qualitative methods and a literature study approach, this article examines primary data from Buddhist texts and secondary sources from academic literature. The main findings suggest that strengthening value-based management can strengthen the position of Buddhist schools as transformative institutions in shaping character and wisdom. This article makes a theoretical contribution by proposing a Dhamma-based strategic framework that is applicable in the Indonesian context.